Pharmacokinetic/Pharmacodynamic Target Attainment of Vancomycin, at Three Reported Infusion Modes, for Methicillin-Resistant Staphylococcus aureus (MRSA) Bloodstream Infections in Critically Ill Patients: Focus on Novel Infusion Mode - Song, Xiangqing; Han, Mi (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To evaluate and compare the pharmacokinetic/pharmacodynamic (PK/PD) exposure of vancomycin, in novel optimal two step infusion (OTSI) v.s. intermittent infusion (II) v.s. continuous infusion (CI) mode, for MRSA bloodstream infections occurring in critical patients. Methods With PK/PD modelling and Monte Carlo simulations, PK/PD exposure of 15 OTSI, 13 II and 6 CI regimens for vancomycin, at 1, 2, 3, 4, 5 and 6 g daily dose, was evaluated. Using the Monte Carlo simulations, the vancomycin population PK parameters derived from critical patients, the PD parameter for MRSA isolates [i.e., minimum inhibitory concentration (MIC)] and the dosing parameters of these regimens were integrated into a robust model of vancomycin PK/PD index, defined as a ratio of daily area under the curve (AUC0-24) to MIC (i.e., AUC0-24/MIC), to estimate the probability of target attainment (PTA) of these regimens against MRSA isolates with an MIC of 0.5, 1, 2, 4 and 8 mg/L in patients with various renal function. The PTA at an AUC0-24/MIC ratio of >400, 400～600 and >600 was estimated. Regimen with a PTA of ≥90% at an AUC0-24/MIC ratio of 400～600, which is supposed to maximize both efficacy and safety, was considered optimal. Results At the same daily dose, almost only the OTSI regimens showed a PTA of ≥90% at an AUC0-24/MIC ratio of 400～600, and this profile seems evident especially in patients with creatinine clearance (CLcr) of ≥60 ml/min and for isolates with an MIC of ≤2 mg/L. However, for patients with CLcr of <60 ml/min and for isolates with an MIC of ≥4 mg/L, the II regimens often displayed a higher or even ≥90% PTA at an AUC0-24/MIC ratio of >400 and also of >600. The CI regimens frequently afforded a reduced PTA at an AUC0-24/MIC ratio of >400 and also of >600, regardless of CLcr and MIC. Conclusions The data indicated that the OTSI regimens allowed preferred PK/PD exposure in terms of both efficacy and safety, and thus should be focus more on especially in patients with CLcr of ≥60 ml/min and for isolates with an MIC of ≤2 mg/L.